A New Methodology for Allocation of Stabilizers in Uncontrollable poles of multi-machine power systems - Nadali Gharahajilo; Hamid Lesani; Mahmood Fotuhi (International Journal of Electrical and Computer Engineering (IJECE), 2013)
One of the main problems in power systems is dynamic stability and damping of Electromechanical  oscillations which for this reason power system stabilizers are being used and the method for determining the location of stabilizer for the purpose of damping critical modes, is using participation factors, in which controllability and observability of modes have influence. The real value or the amplitude of participation factor is usually used as evaluation criterion, while in case that the real values of participation factors are close, the imaginary part of these coefficients are also influential, and if the imaginary part of coefficients are either negative or positive, different results will be obtained. The method introduced in this paper, in modes that the value of participation factors are close to each other, priority for the placement of generator, installation of stabilizer and the optimum value for the stabilizer's gain, is very accurate and appropriate.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1835